Reversible acute renal failure induced by losartan in a renal transplant recipient. Issue 856 (February 1997) - Ostermann, M.; Goldsmith, D. J.; Doyle, T.; Kingswood, J. C.; Sharpstone, P.
Abstract : A 56-year-old man who received a live-related renal transplant in 1988 was started in 1995 on the selective angiotensin II antagonist losartan (Dupont-Merke) to treat worsening hypertension. Two months later because of pulmonary oedema, loop diuretics were started. Within two weeks, serum creatinine had increased from 245 to 571 mumol/l, and the patient became oliguric. A systolic bruit was noted over the graft. Renal angiography showed a 90% stenosis of the transplant renal artery. Losartan was withdrawn, with prompt improvement in renal function. A successful percutaneous transluminal angioplasty performed a few days later resulted in further improvement in renal function accompanied by a significant diuresis.